Orthodox Christian Perspectives on War - Karras, Valerie A.; Hamalis, Perry T., 1970- (Book collections on Project MUSE., 2017)
Through essays written by prominent Orthodox scholars in the fields of biblical studies, church history, Byzantine studies, theology, patristics, political science, ethics, and biology, Orthodox Christian Perspectives on War presents and examines the Orthodox tradition's nuanced and unique insights on the meaning and challenges of war with an eye toward their contemporary relevance.